EVALUATION OF LANDSCAPE ECOLOGICAL POLARIZATION AND ITS APPLICATION FOR STRATEGICAL TERRITORIAL PLANNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
To avoid antagonism in system nature-economy-society the concept of state territory management has to be based on the principles of sustainable and balanced development. The strategy of economy development should follow not only the criteria of economical effectiveness, but also the indexes of ecological stability of the territory.The extent of ecological polarization (measure of landscape stability) is conditioned by the combination of (1) landscape geochemical sensitivity and (2) technogeochemical pressure defined in respective territorial units. With respect to self-cleaning features of landscapes 7 levels of geosystem sensitivity were distinguished and mapped in Lithuania territory. The largest part of the territory is occupied by averagely and more than averagely sensitive geosystems, the least area is taken by relatively insensitive and extremely sensitive geosystems. The technogeochemical pressure was evaluated through the detailed analysis of landscape technomorphological structure. Using the GIS data bases, in the technotopes distinguished the technogeochemical pressure was evaluated according to the area of industrial and built-up territories, agricultural lands, road net density (adjusted by traffic intensity), and dosmestic pollution (assessed according to the population density). Each of the agents was given different weitcoefficients in regard to its pollution emissions. The layer superposition of the geosystem sensitivity and technogeochemical pressure gave the emergence of cartoscheme revealing the distribution of areas with different ecological polarization, divided into 5 tension levels. In order to distinguish the priority territories of land management and optimization the polarization area net and the natural frame of Lithuania were superposed.Knowledge of the ecological polarization areas allows the rendering of recommendations to economy units for their economical activity organization that should be developed considering the means of landscape ecological stability maintenance like increase of forest percentage, formation of geochemical barriers, proper distribution of land use.